Influence of Intercropping System in Unmatured Agarwood Plantation - Elias, Fauzi (Archives of Business Research, 2019)
The study was conducted to investigate the effect of intercropping system between short-term crops and karas trees on the growth of karas trees and the side income made by the karas planters after implementing the intercropping system. There were four treatment groups implemented in this study which include monoculture of karas(control), karas with chilli (T1), karas with okra(T2) and karas with corn (T3). The karas tree growth parameters measured were height (cm), circumference (cm) and leaves count. The production yield of selected short-term crops was weighed in kilogram and the net profit analysis was made based on the market price of chilli, corn and okra. The data collection for the growth of karas tree was done ‘before’ and ‘during’ the plantation of short-term cropsin the study site as well as ‘after’ the short-term crops were removed from the study site.Data analysis showed that there was a significant difference (p<0.05) on the tree circumference after okra and chilliwere removed from the study plotswhen compared to the control group. Besides, chilliwas recorded with the highest net profit of RM 1857.60. Therefore, the intercropping of karas tree with short-term crops can generate profitable side income to karas planters and these intercropping practices are proven to have no negative impact on the growth ofkaras trees in the study site.